A method for preparing adsorption membrane material for pharmaceutical wastewater treatment
By introducing hydrophilic quaternary ammonium salt groups and carboxyl groups on the polyethersulfone microporous membrane, the problems of poor adsorption performance and insufficient anti-pollution performance of traditional membranes on tetracycline are solved, and efficient tetracycline adsorption and antibacterial effects are achieved.
Patent Information
- Application Number
- CN202410872344.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The traditional polyether sulfone microporous membrane has poor adsorption performance on tetracycline, poor hydrophilicity, and insufficient anti-pollution performance. Especially when treating tetracycline-containing pharmaceutical wastewater and medical wastewater, there are protein and bacterial contamination problems.
N,N-bis[2-(imidazole-4,5-dicarboxylate)ethyl]-2-acrylamide was introduced by ultraviolet irradiation graft modification on polyethersulfone microporous membrane, followed by Quaternization reaction and sodium hydroxide hydrolysis are carried out to form hydrophilic quaternary ammonium salt groups and carboxy groups, improving the hydrophilicity and antibacterial properties of the membrane surface.
It significantly improves the hydrophilicity and antibacterial properties of the membrane materials, enhances the adsorption ability to tetracycline, and the interception rate reaches 94.2-98.3%, effectively reduces the adhesion and growth of proteins and bacteria, and improves the anti-pollution performance of the membrane.
Smart Images

Figure BDA0004922005730000031 
Figure BDA0004922005730000041 
Figure BDA0004922005730000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane separation, in particular to a method for preparing an adsorption membrane material used in pharmaceutical wastewater treatment. Background Art
[0002] Tetracycline and its hydrochloride are a class of broad-spectrum antibiotics, which are widely used in the medical field and feed additives. In the actual production process of tetracycline, a small amount of tetracycline and other pharmaceutical pollutants will remain in the pharmaceutical wastewater. Such pollutants are continuously enriched in the water environment, causing great pollution to the natural environment such as soil and water sources. Therefore, it is urgent to efficiently treat tetracycline and other pollutants in pharmaceutical wastewater and medical wastewater.
[0003] Membrane separation is a method of selectively permeating certain components in a liquid using thin film materials. It is widely used in material separation, pollutant adsorption and interception, wastewater treatment, etc. Such as ultrafiltration membrane, permeation membrane, nanofiltration membrane, etc., the film substrates are polyethersulfone, polypropylene, polyethylene, etc. Among them, polyethersulfone microporous membrane has the advantages of strong high temperature resistance, good structural stability, and high mechanical strength. However, the traditional polyethersulfone microporous separation membrane has a low force on tetracycline, and the adsorption and interception performance is poor. It is greatly restricted in pharmaceutical wastewater and medical wastewater containing tetracycline. In addition, in the actual membrane separation application process, when separating biological products, protein and bacterial microbial contamination will occur, which will affect the performance of the separation membrane. Therefore, it is necessary to improve the antimicrobial contamination of microporous membrane materials. Introducing hydrophilic groups on the membrane surface to improve its hydrophilicity can reduce the adhesion of protein and bacterial pollutants, which is conducive to improving the antibacterial and antimicrobial contamination of membrane materials. Summary of the invention
[0004] The invention solves the problems that the polyethersulfone membrane material has poor adsorption performance for pollutants such as tetracycline, poor hydrophilicity, poor anti-pollution performance, etc.
[0005] The technical solution of the present invention is: a method for preparing an adsorption film material, comprising the following steps:
[0006] Step S1, add ethanol, N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide, and benzophenone into a reaction bottle, stir and dissolve to obtain a grafting solution, introduce nitrogen, add a polyethersulfone microporous membrane, and then irradiate the solution under ultraviolet light to carry out a grafting reaction, take out the microporous membrane, wash it with xylene and ethanol in turn, and dry it to obtain an imidazole dimethyl carboxylate-modified polyethersulfone microporous membrane.
[0007] Step S2, add N,N-dimethylformamide and imidazole dimethyl carboxylate modified polyethersulfone microporous membrane into a reaction bottle, heat to the reaction temperature, stir for 3-5 hours, add the brominated alkyl compound, cool the solution in an ice water bath after the reaction, filter, wash with ethanol, and dry to obtain a quaternary ammonium salt imidazole dimethyl carboxylate modified polyethersulfone microporous membrane.
[0008] Step S3, add sodium hydroxide aqueous solution and quaternary ammonium salt imidazole dimethyl dicarboxylate modified polyethersulfone microporous membrane to the reaction bottle, heat to the reaction temperature, add dilute hydrochloric acid to neutralize the solution to pH 4-5 after the reaction, filter, wash with distilled water, and dry to obtain an adsorption membrane material. The reaction mechanism is as follows:
[0009]
[0010] Furthermore, in step S1, the mass concentration of N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester)ethyl]-2-acrylamide in the grafting solution is (15-200) g / L, and the mass concentration of benzophenone is (0.11-16) g / L.
[0011] Furthermore, in step S1, the power of the ultraviolet lamp is 300-600W, and the grafting reaction time is 8-15 minutes.
[0012] Further, in step S2, the mass of the bromoalkyl compound is 3-42% of the mass of the imidazole dimethyl carboxylate modified polyethersulfone microporous membrane; the molecular formula of the bromoalkyl compound is C n H 2n+1 Br, n is any integer from 6 to 10.
[0013] Furthermore, in step S2, the reaction temperature is 110-140° C., and the reaction time is 36-72 h.
[0014] Furthermore, in step S3, the mass concentration of the sodium hydroxide aqueous solution is (40-65) g / L.
[0015] Furthermore, in step S3, the reaction temperature is 70-85° C., and the reaction time is 4-10 h.
[0016] Further, the preparation method of N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide is as follows: add acetonitrile, 1H-imidazole-4,5-dicarboxylic acid dimethyl ester, N,N-bis(2-chloroethyl)-2-acrylamide, and potassium carbonate to a reaction bottle, react at 25-40°C for 48-72h, rotary evaporate the solution, wash with distilled water, dry, and recrystallize the product in ethyl acetate to obtain N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide. The reaction formula is as follows:
[0017]
[0018] Furthermore, the masses of dimethyl 1H-imidazole-4,5-dicarboxylate and potassium carbonate are 185-195% and 140-160% of the mass of N,N-bis(2-chloroethyl)-2-acrylamide, respectively.
[0019] Furthermore, the application of adsorption membrane materials in pharmaceutical wastewater.
[0020] The technical effect of the present invention is as follows: the present invention utilizes N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide for ultraviolet radiation grafting modification, and then utilizes 1-bromohexane or the like to carry out quaternization reaction on the imidazole group, introduces a hydrophilic quaternary ammonium salt group, and generates a large number of hydrophilic carboxyl groups through sodium hydroxide hydrolysis, thereby realizing the introduction of a large number of hydrophilic groups such as amide bonds, quaternary ammonium salts, and carboxyl groups on the surface of the polyethersulfone microporous membrane. The surface hydrophilicity of the adsorption membrane is significantly improved, and a lower water contact angle is exhibited. The lower the water contact angle, the better the hydrophilicity of the membrane material, and a hydrophilic layer can be formed on the membrane surface, which is beneficial to reducing the adhesion of proteins on the membrane surface. At the same time, the hydrophilic layer reduces the adsorption and growth and reproduction of microorganisms such as bacteria on the surface of the membrane material, which is beneficial to improving the anti-protein pollution and anti-biological pollution effects of the membrane material.
[0021] The surface of the adsorption membrane material of the invention contains a large number of antibacterial quaternary ammonium salt groups, which significantly improves the antibacterial rate of the polyethersulfone microporous membrane material to Escherichia coli and Staphylococcus aureus, and exhibits excellent antibacterial and anti-biological pollution performance.
[0022] The polyethersulfone microporous adsorption membrane of the present invention contains a large number of carboxyl groups, which can interact with the hydroxyl group and the amide group of tetracycline hydrochloride by hydrogen bonding. At the same time, the carboxyl groups are negatively charged, while tetracycline hydrochloride is positively charged, and the two can form an electrostatic interaction, which significantly improves the adsorption performance of the adsorption membrane for tetracycline hydrochloride. When the solution is 10-100 mg / L, the interception rate reaches up to 94.2-98.3%. The polyethersulfone microporous membrane has better practical application in pharmaceutical wastewater and medical wastewater containing tetracycline. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] The structural formula of dimethyl imidazole-4,5-dicarboxylate of the present invention is The CAS registration number is 3304-70-9.
[0025] The structural formula of N,N-bis(2-chloroethyl)-2-acrylamide is The CAS registration number is 2727079-70-9.
[0026] The pore size of polyethersulfone microporous membrane is 0.22um.
[0027] Example 1
[0028] (1) Add 80 mL of acetonitrile, 2 g of 1H-imidazole-4,5-dicarboxylic acid dimethyl ester, 3.9 g of N,N-bis(2-chloroethyl)-2-acrylamide, and 3.2 g of potassium carbonate to a reaction bottle, react at 25° C. for 72 h, rotary evaporate the solution, wash with distilled water, dry, and recrystallize the product in ethyl acetate to obtain N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester)ethyl]-2-acrylamide.
[0029] (2) Add ethanol, N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide and benzophenone into the reaction bottle, stir and dissolve, control the mass concentration of N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide in the solution to be 15 g / L, and the mass concentration of benzophenone to be 0.11 g / L, introduce nitrogen, add polyethersulfone microporous membrane, and then irradiate the solution under a 300 W ultraviolet lamp to carry out grafting reaction for 10 minutes, take out the microporous membrane, wash it with xylene and ethanol in turn, and dry it to obtain imidazole dimethyl carboxylate modified polyethersulfone microporous membrane.
[0030] (3) Add 500 mL of N,N-dimethylformamide and 30 g of dimethyl imidazole dicarboxylate-modified polyethersulfone microporous membrane to the reaction bottle, heat to 120 °C, stir for 3 h, and then add 0.9 g of 1-bromohexane (C 6 H 13 Br), react for 48 hours, cool the solution in an ice-water bath, filter, wash with ethanol, and dry to obtain a quaternary ammonium salt imidazole dimethyl carboxylate modified polyethersulfone microporous membrane.
[0031] (4) Add 800 mL of 40 g / L sodium hydroxide aqueous solution and 10 g of quaternary ammonium salt imidazole dimethyl dicarboxylate modified polyethersulfone microporous membrane into the reaction bottle, heat to 70 ° C, react for 10 h, add dilute hydrochloric acid to neutralize the solution to pH 5, filter, wash with distilled water, and dry to obtain an adsorption membrane material.
[0032] Example 2
[0033] (1) Add 80 mL of acetonitrile, 2 g of 1H-imidazole-4,5-dicarboxylic acid dimethyl ester, 3.7 g of N,N-bis(2-chloroethyl)-2-acrylamide, and 2.8 g of potassium carbonate to a reaction flask, react at 40° C. for 48 h, rotary evaporate the solution, wash with distilled water, dry, and recrystallize the product in ethyl acetate to obtain N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester)ethyl]-2-acrylamide.
[0034] (2) Add ethanol, N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide and benzophenone into the reaction bottle, stir and dissolve, control the mass concentration of N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide in the solution to be 120 g / L, and the mass concentration of benzophenone to be 0.95 g / L, introduce nitrogen, add polyethersulfone microporous membrane, and then irradiate the solution under a 300 W ultraviolet lamp to carry out grafting reaction for 15 minutes, take out the microporous membrane, wash it with xylene and ethanol in turn, and dry it to obtain imidazole dimethyl carboxylate modified polyethersulfone microporous membrane.
[0035] (3) Add 600 mL of N,N-dimethylformamide and 30 g of dimethyl imidazole dicarboxylate modified polyethersulfone microporous membrane to the reaction bottle, heat to 140°C, stir for 3 h, and then add 8.2 g of 1-bromooctane (C 8 H 17 Br), react for 36 hours, cool the solution in an ice-water bath, filter, wash with ethanol, and dry to obtain a quaternary ammonium salt imidazole dimethyl carboxylate modified polyethersulfone microporous membrane.
[0036] (4) Add 800 mL of 55 g / L sodium hydroxide aqueous solution and 10 g of quaternary ammonium salt imidazole dimethyl carboxylate modified polyethersulfone microporous membrane into the reaction bottle, heat to 80 ° C, react for 4 hours, add dilute hydrochloric acid to neutralize the solution to pH 4, filter, wash with distilled water, and dry to obtain an adsorption membrane material.
[0037] Example 3
[0038] (1) Add ethanol, N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide (prepared in the same manner as in Example 1) and benzophenone into a reaction bottle, stir and dissolve, control the mass concentration of N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide in the solution to be 200 g / L, and the mass concentration of benzophenone to be 16 g / L, introduce nitrogen, add a polyethersulfone microporous membrane, and then irradiate the solution under a 500 W ultraviolet lamp to carry out a grafting reaction for 8 minutes, take out the microporous membrane, wash it with xylene and ethanol in turn, and dry it to obtain a dimethyl imidazole dicarboxylate modified polyethersulfone microporous membrane.
[0039] (2) Add 600 mL of N,N-dimethylformamide and 30 g of dimethyl imidazole dicarboxylate modified polyethersulfone microporous membrane to the reaction bottle, heat to 110°C, stir for 5 h, and then add 12.6 g of 1-bromodecane (C 10 H 21 Br), react for 72 hours, cool the solution in an ice-water bath, filter, wash with ethanol, and dry to obtain a quaternary ammonium salt imidazole dimethyl carboxylate modified polyethersulfone microporous membrane.
[0040] (3) Add 800 mL of 65 g / L sodium hydroxide aqueous solution and 10 g of quaternary ammonium salt imidazole dimethyl dicarboxylate modified polyethersulfone microporous membrane into the reaction bottle, heat to 85 ° C, react for 6 h, add dilute hydrochloric acid to neutralize the solution to pH 4, filter, wash with distilled water, and dry to obtain an adsorption membrane material.
[0041] Comparative Example 1 is a polyethersulfone microporous membrane that has not been grafted and modified.
[0042] Comparative Example 2 is a polyethersulfone microporous membrane modified by dimethyl imidazole dicarboxylate (prepared in the same manner as in Example 1).
[0043] Comparative Example 3 is a polyethersulfone microporous membrane modified by quaternary ammonium salt dimethyl imidazole dicarboxylate (prepared in the same manner as in Example 1).
[0044] Comparative Example 4
[0045] (1) Add ethanol, acrylic acid and benzophenone to a reaction bottle, stir and dissolve, control the mass concentration of acrylic acid in the solution to be 15 g / L, and the mass concentration of benzophenone to be 0.11 g / L, introduce nitrogen, add a polyethersulfone microporous membrane, and then irradiate the solution under a 300 W ultraviolet lamp to carry out a grafting reaction for 10 minutes, take out the microporous membrane, wash it with xylene and ethanol in turn, and dry it to obtain a polyacrylic acid modified polyethersulfone microporous membrane.
[0046] The water contact angle of the membrane material was tested by the bubble capture method using a contact angle meter. Each sample was tested 5 times and the average value was taken.
[0047] Table 1 Water contact angle test of membrane materials
[0048] Water contact angle (°) Example 1 50.2 Example 2 41.3 Example 3 40.5 Comparative Example 1 67.6 Comparative Example 2 72.8 Comparative Example 3 63.7 Comparative Example 4 52.2
[0049] As shown in Table 1, the polyethersulfone microporous membrane of Comparative Example 1 has not been subjected to ultraviolet irradiation grafting modification, and its water contact angle is 67.6°.
[0050] Example 1-3 uses N, N-bis [2- (imidazole-4, 5-dicarboxylic acid dimethyl ester) ethyl] -2-acrylamide for ultraviolet irradiation grafting modification, and then uses 1-bromohexane or the like to quaternize the imidazole group, introduces a hydrophilic quaternary ammonium salt group, and is hydrolyzed by sodium hydroxide to generate a large number of hydrophilic carboxyl groups, which significantly improves the surface hydrophilicity of the adsorption film and shows a lower water contact angle. The lower the water contact angle, the better the hydrophilicity of the membrane material, and a hydrophilic layer can be formed on the membrane surface, which is beneficial to reducing the adhesion of proteins on the membrane surface. At the same time, the hydrophilic layer reduces the adsorption and growth of microorganisms such as bacteria on the surface of the membrane material, which is beneficial to improving the anti-protein pollution and anti-biological pollution effects of the membrane material.
[0051] Comparative Example 2 uses N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide to perform ultraviolet irradiation grafting modification on the polyethersulfone microporous membrane, which does not contain hydrophilic quaternary ammonium salt groups and carboxyl groups, has a water contact angle of 72.8°, and has poor hydrophilicity.
[0052] The microporous membrane of Comparative Example 3 has not been hydrolyzed, does not contain hydrophilic carboxyl groups, and only contains hydrophilic quaternary ammonium salt groups. The water contact angle is 63.7°, which is lower than that of Comparative Examples 1 and 2, but higher than that of each embodiment, and the hydrophilicity is poor.
[0053] In Comparative Example 4, acrylic acid was used to irradiate and graft polyethersulfone to introduce hydrophilic carboxyl groups on the membrane surface. The water contact angle of the membrane material was significantly reduced, but it was slightly higher than that of Example 1. This may be because N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide contains four ester groups, which can produce four carboxyl groups after hydrolysis, thereby introducing more carboxyl groups on the surface of the microporous membrane. In addition, the polyacrylic acid modified polyethersulfone microporous membrane does not contain hydrophilic amide bonds and quaternary ammonium salt groups, resulting in a higher water contact angle than that of Example 1.
[0054] The film coating method was used to test the antibacterial properties of the membrane material against the test bacteria, which were Escherichia coli or Staphylococcus aureus.
[0055] The membrane material was cut into 10 cm circular membranes, immersed in 80% ethanol solution for disinfection and sterilization, and then dried. The slant-preserved test strains were inoculated into agar medium, cultured and activated for 24 hours, and then 2 rings were transferred to physiological saline culture medium containing nutrient broth and gradiently diluted to 10 6 cfu of bacterial solution. Then transfer 0.2mL of bacterial solution to the surface of the membrane material, cover it with a sterilized polyethylene film, and culture it in a constant temperature and humidity incubator at 37℃ for 24h. After culture, elute the bacteria on the surface of the membrane with physiological saline eluent, then transfer 1mL of the eluted bacterial solution, place it in an agar medium, and culture it at 37℃ for 48h. Calculate the antibacterial rate W. W=(BC) / B×100%.
[0056] B is the average number of recovered bacteria (cfu / piece) of the blank control sample, and the polyethersulfone microporous membrane of Comparative Example 1 is the blank control sample.
[0057] C is the average number of recovered bacteria in the test samples (cfu / plate).
[0058] Table 2 Antibacterial test of membrane materials
[0059]
[0060] As shown in Table 2, the membrane materials of Examples 1-3 and Comparative Example 3 all contain a large amount of antibacterial quaternary ammonium salt groups, which significantly improve the antibacterial rate of the polyethersulfone microporous membrane material against Escherichia coli and Staphylococcus aureus, showing excellent antibacterial and anti-biological contamination properties.
[0061] The polyethersulfone microporous membrane materials of Comparative Examples 2 and 4 do not contain antibacterial quaternary ammonium salt groups and show almost no antibacterial rate against Escherichia coli and Staphylococcus aureus.
[0062] Add tetracycline hydrochloride to distilled water to prepare a tetracycline hydrochloride solution with a mass concentration of 10-100 mg / L. Use an ultrafiltration cup to filter the tetracycline hydrochloride solution with a membrane material at a pressure of 0.1 MPa and a test temperature of room temperature. Pre-press the membrane material with distilled water before filtration at a pressure of 0.3 MPa for 30 minutes. Calculate the retention rate Q of the membrane material for tetracycline hydrochloride. Q = (C 0 -C) / C 0 . C 0 is the initial concentration of the solution. C is the concentration of the filtrate after filtration.
[0063]
[0064]
[0065] The polyethersulfone microporous membrane of Comparative Example 1 was not subjected to ultraviolet irradiation grafting modification. When the solution concentration was 10 mg.L, the retention rate of tetracycline hydrochloride was 78.4%.
[0066] The polyethersulfone microporous adsorption membrane of Examples 1-3 contains a large number of carboxyl groups, which can interact with the hydroxyl and amide groups of tetracycline hydrochloride by hydrogen bonds. At the same time, the carboxyl groups are negatively charged, while tetracycline hydrochloride is positively charged. The two can form an electrostatic interaction, which significantly improves the adsorption performance of the adsorption membrane for tetracycline hydrochloride. When the solution is 10-100 mg / L, the retention rate is as high as 94.2-98.3%.
[0067] The polyethersulfone microporous membranes of Comparative Examples 2 and 3 do not contain carboxyl groups, and have poor adsorption performance for tetracycline hydrochloride and low retention rates.
[0068] The above-mentioned embodiments only express several implementation methods of the present invention, but the implementation methods of the present invention are not limited by the above-mentioned embodiments. Any other changes made without departing from the spirit and principle of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing an adsorption film material, characterized in that: The preparation method of the adsorption film material comprises the following steps: Step S1, adding ethanol, N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide, and benzophenone into a reaction bottle, stirring and dissolving to obtain a grafting solution, introducing nitrogen gas, adding a polyethersulfone microporous membrane, and then irradiating the solution under ultraviolet light to carry out a grafting reaction, taking out the microporous membrane, washing, and drying to obtain a polyethersulfone microporous membrane modified with imidazole dimethyl carboxylate; Step S2, adding N,N-dimethylformamide and imidazole dimethyl carboxylate modified polyethersulfone microporous membrane into a reaction bottle, heating to the reaction temperature, adding a brominated alkyl compound after stirring, cooling the solution after the reaction, filtering, washing, and drying to obtain a quaternary ammonium salt imidazole dimethyl carboxylate modified polyethersulfone microporous membrane; Step S3, adding sodium hydroxide aqueous solution and quaternary ammonium salt imidazole dimethyl carboxylate modified polyethersulfone microporous membrane into the reaction bottle, heating to the reaction temperature, adding dilute hydrochloric acid to neutralize after the reaction, filtering, washing, and drying to obtain an adsorption membrane material; In step S2, the mass of the bromoalkyl compound is 3-42% of the mass of the polyethersulfone microporous membrane modified with dimethyl imidazole dicarboxylate; the molecular formula of the bromoalkyl compound is C n H 2n+1 Br, n is any integer from 6 to 10.
2. The method for preparing an adsorption film material according to claim 1, characterized in that: In the step S1, the mass concentration of N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester)ethyl]-2-acrylamide in the grafting solution is 15-200 g / L, and the mass concentration of benzophenone is 0.11-16 g / L.
3. The method for preparing an adsorption film material according to claim 1, characterized in that: In the step S1, the power of the ultraviolet lamp is 300-600W, and the grafting reaction time is 8-15 minutes.
4. The method for preparing an adsorption film material according to claim 1, characterized in that: In step S2, the reaction temperature is 110-140° C., and the reaction time is 36-72 hours.
5. The method for preparing an adsorption film material according to claim 1, characterized in that: In step S3, the mass concentration of the sodium hydroxide aqueous solution is 40-65 g / L.
6. The method for preparing an adsorption film material according to claim 1, characterized in that: In step S3, the reaction temperature is 70-85° C. and the reaction time is 4-10 h.
7. The method for preparing an adsorption film material according to claim 2, characterized in that: The preparation method of N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide comprises the following steps: adding acetonitrile, 1H-imidazole-4,5-dicarboxylic acid dimethyl ester, N,N-bis(2-chloroethyl)-2-acrylamide and potassium carbonate into a reaction bottle, reacting at 25-40° C. for 48-72 hours, rotary evaporating the solution, washing, drying and recrystallizing to obtain N,N-bis[2-(imidazole-4,5-dicarboxylic acid dimethyl ester) ethyl]-2-acrylamide.
8. The method for preparing an adsorption film material according to claim 7, characterized in that: The masses of the 1H-imidazole-4,5-dicarboxylic acid dimethyl ester and potassium carbonate are 185-195% and 140-160% of the mass of N,N-bis(2-chloroethyl)-2-acrylamide respectively.
9. Use of the adsorption membrane material obtained by the preparation method according to any one of claims 1 to 8 in pharmaceutical wastewater.
